Implementation Of Good Corporate Governance Principles At Pratama Clinic Bekasi: Accountability Principle - Zulhilmi Majdan, Muhammad; Kusumaningtyas, Rohmawati; Kim Danh, Nguyen Thi (International Economic Conference of Business and Accounting, 2024)
The purpose of this study was to reveal the implementation of Good Corporate Governance (GCG) in Pratama Clinic at Bekasi. This study applied Stakeholders proposed by Freeman et.al and Jensen & Meckling’s Agency. The research design was descriptive qualitative methods. Data collection techniques were interviews and observation. The results of this study showed that the Clinic has implemented 3 out of 5 the principles of GCG, namely fairness, responsibility and independence. However, another 2 principles have not run optimally. The first one is the principle of accountability. The clinic allows one employee hold multiple position since the clinic unable to clearly track the organizational structure in a clear. The second is the principle of transparency in which the financial reports limited to be known by the financial manager, director and commissioner. The last but not the least the clinic may use of an abundance of information about quality transparency through consumer reports.